2022
DOI: 10.3389/fmolb.2022.781039
|View full text |Cite
|
Sign up to set email alerts
|

Computational Repurposing of Drugs and Natural Products Against SARS-CoV-2 Main Protease (Mpro) as Potential COVID-19 Therapies

Abstract: We urgently need to identify drugs to treat patients suffering from COVID-19 infection. Drugs rarely act at single molecular targets. Off-target effects are responsible for undesirable side effects and beneficial synergy between targets for specific illnesses. They have provided blockbuster drugs, e.g., Viagra for erectile dysfunction and Minoxidil for male pattern baldness. Existing drugs, those in clinical trials, and approved natural products constitute a rich resource of therapeutic agents that can be quic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 92 publications
(108 reference statements)
0
10
0
Order By: Relevance
“…Literature analysis of the modes of action of these classes, and published work on their efficacy against SARS-CoV-2, provide mechanistic information and validate our computational screening approach as useful for identifying repurposing candidates. This approach was adopted in our published repurposing studies on the SARS-CoV-2 main protease (M pro ), helicase, and RNA-dependent RNA polymerase [ 8 , 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature analysis of the modes of action of these classes, and published work on their efficacy against SARS-CoV-2, provide mechanistic information and validate our computational screening approach as useful for identifying repurposing candidates. This approach was adopted in our published repurposing studies on the SARS-CoV-2 main protease (M pro ), helicase, and RNA-dependent RNA polymerase [ 8 , 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have reported computational studies on S protein and ACE2 to elucidate the origins of SARS-CoV-2 and identify repurposed drugs inhibiting its main protease, RNA-dependent RNA polymerase, and helicase [ 8 , 9 , 10 , 11 ]. Here, we used the S protein FABP structure to identify repurposing candidates as SARS-CoV-2 treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Cynarine, eravacycline, and prexasertib represented outstanding inhibitory activity with IC 50 values of 1.82 μ M, 1.65 μM, and 1.99 μM, respectively. Interestingly, eravacycline was also identified in recent virtual screens of FDA-approved drugs for repurposing as COVID-19 treatments [ 14 , 15 ]. The docking modes of cynarine, eravacycline, and prexasertib indicated that between the two catalytic dyad residues His41 and Cys145, Cys145 was involved in binding with all three chemicals ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Docking studies, similarly, largely favored prioritizing the M pro as the target in their screenings, although many drugs were demonstrated to have inhibitory effects against a different viral protein. Remdesivir, for example, which was cocrystallized with RdRp, appeared in numerous M pro computational docking campaigns as a predicted hit. On the other hand, it is possible that identified drugs in a target-specific virtual repurposing campaign could act synergistically on more than one SARS-CoV-2 targeas speculated for chloroquine inhibiting M pro activity and interfering with the endosomal acidification process associated with SARS-CoV-2 viral entry . The lack of sufficient biochemical data, in turn, may render it challenging to rule out off-target activity.…”
Section: Target-based Sars-cov-2 Repositioning Screeningsmentioning
confidence: 99%
“…These molecules were active in cell-based repurposing screenings: dolutegravir, elbasvir, nelfinavir, atazanavir, lopinavir, ritonavir, darunavir, saquinavir, indinavir, oseltamivir, chloroquine, and remdesivir (Figure ). ,,,,,,,,,, ,, …”
Section: Target-based Sars-cov-2 Repositioning Screeningsmentioning
confidence: 99%